The Impact of Pro-Competitive Reforms on Trade in Developing Countries - Miroudot, Sébastien (OECD Trade Policy Papers, 2007)
This report proposes an analysis of the mutually reinforcing relationship between trade, investment and competition policies and how together they impact trade in developing countries. An index of pro-competitive reforms is provided for 82 countries over the period 2001-2005. The index synthesises 13 indicators of the policy stance of countries with regard to trade, investment and competition. It is then used in quantitative analysis to determine the impact of barriers to competitive markets on trade. The results shows that there are substantial gains for developing countries in market and regulatory reforms in terms of higher trade flows and higher income per capita. Moreover, the paper further examines pro-competitive reforms in key services sectors and the extent to which trade agreements can promote them through the experience of the WTO telecoms Reference Paper. The analysis highlights that countries achieved a high degree of liberalisation in the telecoms sector and that regulatory principles of the Reference Paper were useful in promoting sound policies under domestic regulatory reforms of the sector